2009
DOI: 10.1021/es9010543
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Developmental Defects of Different Sizes and Shape Nickel Nanoparticles in Zebrafish

Abstract: Metallic nanoparticles such as nickel are used in catalytic, sensing and electronic applications, but health and environmental affects have not been fully investigated. While some metal nanoparticles result in toxicity, it is also important to determine whether nanoparticles of the same metal but of different size and shape changes toxicity. Three different size nickel nanoparticle (Ni NPs) of 30, 60, and 100 nm and larger particle clusters of aggregated 60 nm entities with a dendritic structure were synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(156 citation statements)
references
References 36 publications
(55 reference statements)
9
147
0
Order By: Relevance
“…The exposure to differently sized nickel NP as well as larger particle clusters of aggregated entities with a dendritic structure revealed a higher toxicity level than any of the other particle forms or sizes ( table 1 ). As there were no significant differences in toxicities of nickel NP of different size, the spatial configuration of the NP probably affected toxicity more than their size [Ispas et al, 2009]. On the other hand, a size-dependent Asharani et al [2008a] 10 μg/ml slight increase in lethality (about 20% embryos), embryos with slimy coating and brown specks 25 μg/ml increase in lethality (about 40% embryos) 50 μg/ml increase in lethality (about 70%), hatching delay, abnormal body axes and twisted notochord (>50 μg/ml), slow blood flow, yolk sac distorted, heart rate decreased and apoptosis in the skin (>50 μg/ml) 100 μg/ml increase in lethality (about 85% toxic effect was confirmed in zebrafish in the case of using silver NP [Lee et al, 2012a].…”
Section: Factors Influencing the Embryonic Toxicity Of Npmentioning
confidence: 94%
See 1 more Smart Citation
“…The exposure to differently sized nickel NP as well as larger particle clusters of aggregated entities with a dendritic structure revealed a higher toxicity level than any of the other particle forms or sizes ( table 1 ). As there were no significant differences in toxicities of nickel NP of different size, the spatial configuration of the NP probably affected toxicity more than their size [Ispas et al, 2009]. On the other hand, a size-dependent Asharani et al [2008a] 10 μg/ml slight increase in lethality (about 20% embryos), embryos with slimy coating and brown specks 25 μg/ml increase in lethality (about 40% embryos) 50 μg/ml increase in lethality (about 70%), hatching delay, abnormal body axes and twisted notochord (>50 μg/ml), slow blood flow, yolk sac distorted, heart rate decreased and apoptosis in the skin (>50 μg/ml) 100 μg/ml increase in lethality (about 85% toxic effect was confirmed in zebrafish in the case of using silver NP [Lee et al, 2012a].…”
Section: Factors Influencing the Embryonic Toxicity Of Npmentioning
confidence: 94%
“…The impact of NP size was shown in zebrafish embryos [Ispas et al, 2009]. The exposure to differently sized nickel NP as well as larger particle clusters of aggregated entities with a dendritic structure revealed a higher toxicity level than any of the other particle forms or sizes ( table 1 ).…”
Section: Factors Influencing the Embryonic Toxicity Of Npmentioning
confidence: 97%
“…ICP-MS is a type of mass spectrometry that has been widely used for determination and quantification of inorganic nanoparticles such as gold and nickel particles [167][168][169]. However, ICP-MS is not widely used for the measurement of inorganic nanoparticles.…”
Section: Inductively Coupled Plasma-mass Spectrometrymentioning
confidence: 99%
“…Nanomaterials are theoretically expected to be more toxic than their bulk counterparts due to their greater surface reactivity and the ability to penetrate into and accumulate within cells and organisms (Carlson et al, 2008;Ispas et al, 2009;Mironava et al, 2010). However, investigations of aggregations of NPs with size distributions similar to those of their bulk particles in suspension have revealed that the toxicity mechanisms of NPs are more complex (Warheit et al, 2006;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%